Intraoperative decision making in bariatric surgery - Al Samaraee, Ahmad (Qatar Med J, 2020)
Background: Surgeons may encounter unexpected anatomical or pathological findings during various bariatric surgical procedures for which they must make prompt and critical decisions that had not been planned prior to the operation. In this practice review, we present our experiences with unexpected challenges and on-table decision making in bariatric surgery to share our knowledge with colleagues who may encounter the same challenges during bariatric surgery. This paper's content is of applied learning and practical value focusing on challenging intraoperative decision making; however, it does not discuss the details of the various techniques used during surgery. Methods: This work is a single-center retrospective review of operations carried out on patients who had unexpected intraoperative findings during bariatric surgery despite the implementation of detailed preoperative evaluations that would have otherwise suggested standard procedures. These findings resulted in abandoned surgery or laparoscopic sleeve gastrectomy instead of the intended Roux-en-Y gastric bypass. Results: A total of 449 patients had received various bariatric interventions in our unit between 2012 and 2016. Eleven patients, representing approximately 2.4% of the total number of patients surveyed had met the inclusion criteria and were added to the final list for analysis. The mean age of the included patients was 40.82 years (range: 30–51 years), and seven of the patients, representing approximately 63.6% of the included cases, were female. The mean body mass index of the 11 cases was 40.8 (range: 38–48). Only two cases (18.9%) had had their surgery abandoned; the rest (81.1%) had received laparoscopic sleeve gastrectomy instead of Roux-en-Y gastric bypass. None of the 11 patients had perioperative morbidity or mortality. Conclusion: Intraoperative decision making for unexpected findings in bariatric surgery is challenging. In these circumstances, surgeons must make prompt and critical decisions, including abandoning the operation. The available literature on this subject is unsurprisingly limited because of the rarity of such findings.